CO2 Electrolysis Cells: Enhancing Electrochemical CO2 Reduction using Ce(Mn, Fe)O2 with La(Sr)Cr(Mn)O3 Cathode for High‐Temperature Solid Oxide Electrolysis Cells (Adv. Energy Mater. 24/2021). Issue 24 (24th June 2021) - Lee, Seokhee; Kim, Minkyu; Lee, Kang Taek; Irvine, John T. S.; Shin, Tae Ho
Abstract : In article number 2100339, Kang Taek Lee, Tae Ho Shin and co‐workers design a promising robust ceramic electrode for high‐temperature CO2 electrolysis cells with a LaGaO3 based solid oxide electrolyte. The presence of the resulting oxygen vacancy enhancement via Mn and Fe co‐doped cerium oxide, Ce(Mn, Fe)O2, mixing with La(Sr)Cr(Mn)O3 perovskite oxide not only provides excellent electrochemical performance but also alleviates issues regarding carbon coking and CO‐CO2 chemisorption reactions.